2019
DOI: 10.1097/ogx.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid for the Prevention of Blood Loss After Vaginal Delivery

Abstract: (Abstracted from N Engl J Med 2018;379:731–742) The use of tranexamic acid (TXA) reduces mortality in the setting of postpartum hemorrhage (PPH). This study investigated whether the prophylactic administration of TXA in addition to prophylactic oxytocin in women with vaginal delivery would decrease the incidence of PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
1
22
0
4
Order By: Relevance
“…11,12 TXA, alone or in conjunction with additional hemostatic therapies, enhances clot stability in whole blood from people with hemophilia. 13 TXA also reduces heavy menstrual bleeding, 14 perioperative blood loss following elective vaginal or cesarean delivery, [15][16][17] and death from postpartum hemorrhage. 18,19 However, TXA does not show survival benefit in patients with acute gastrointestinal bleeding 20 or in some studies of trauma.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 TXA, alone or in conjunction with additional hemostatic therapies, enhances clot stability in whole blood from people with hemophilia. 13 TXA also reduces heavy menstrual bleeding, 14 perioperative blood loss following elective vaginal or cesarean delivery, [15][16][17] and death from postpartum hemorrhage. 18,19 However, TXA does not show survival benefit in patients with acute gastrointestinal bleeding 20 or in some studies of trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The Tranexamic Acid for Preventing Postpartum Hemorrhage Following a Vaginal Delivery (TRAAP) trial enrolled 4079 laboring women who received tranexamic acid or placebo in addition to prophylactic oxytocin after delivery. PPH occurred in 8.5% of the tranexamic acid group vs 9.8% of the placebo group, and this difference was not statically significant (RR 0.83, 95% CI 0.68–1.01) 19 . However, a subsequent meta‐analysis of four clinical trials (N=4671) published by Saccone and colleagues found that women who received prophylactic tranexamic acid after vaginal delivery had a significantly lower risk of PPH (RR 0.61, 95% CI 0.41–0.91) 20 .…”
Section: Tranexamic Acid: Expanding Prevention and Treatment Options mentioning
confidence: 86%
“…Although the use of tranexamic acid did not result in a significantly lower rate of blood loss of at least 500 ml than in the placebo group (relative risk [RR] 0.83; 95% CI 0.68–1.01; P = 0.07), it was nevertheless associated with lower rates of secondary outcomes such as provider‐assessed clinically significant postpartum haemorrhage (RR 0.74; 95% CI 0.61–0.91; P = 0.04 after adjustment for multiple comparisons). Altogether, these results suggested that routine administration of tranexamic acid in addition to an uterotonic may be cost‐effective 4 …”
Section: Introductionmentioning
confidence: 88%